(Invited) Conceptual Learning of Mechanistic and Synthetic Applications of Electrochemistry - Rafiee, Mohammad (Meeting abstracts (Electrochemical Society), 2023)
Electroorganic chemistry is a multidisciplinary science that bridges the fields of electroanalytical chemistry, material science, and organic chemistry. From a synthetic perspective, its principal aim is to provide an environmentally benign alternative to classic organic synthesis by avoiding wasteful reagents. Controlling the electrochemical parameters, current and potential, allows access to mild reaction conditions as well as highly reactive intermediates and reagents. Moreover, the current flowing through the electrode surface is an easy-to-gauge quantity that offers a unique mechanistic tool for the study of the redox reactions and their coupled chemical reactions. Electroanalytical techniques provide unique mechanistic tools to synthetic chemists for studying reactions involving redox active species. The field has experienced a recent surge among the chemists, however, many of the students and professionals are not trained in electrochemistry and are unfamiliar with these tools and the valuable information they can provide. In this talk, I will present a narrative of our recent progress and attempts on designing laboratory experiments and activities for teaching the concepts of organic electrochemistry. The works will be presented include the following subjects. a) Visualizing the diffusion layer and electrode reaction using electricity driven color change reactions under optical microscope. This work allowed to observe the effect of electrochemical reactions at the electrode surface, measure the thickness of diffusion layer, and demonstrate its correlation with Cottrell equation. b) Conceptual presentation of scan rate dependence of voltammetric currents. The aim of this simulation and activity was convoluting the current−time profiles of cyclic voltammetry, aided in visualization of the changes in concentration profiles and concentration gradients of electroactive compounds at the electrode surface by changing the scan rate of voltammetric experiments. This activity aided students in understanding the scan rate dependence of voltammetric current. 1 c) Deriving the Turnover Frequency of electrocatalytic reactions by Chronoamperometry. A laboratory experiment was developed to provide students with an example of how electroanalytical techniques, herein chronoamperometry, can be used for quantitative analysis of a catalytic reaction and for the derivation of the turnover frequency (TOF). 2 d) A laboratory experiment on exploring electrosynthesis showcasing electrochemical methoxylation of carbamates. This laboratory experiment deals with voltammetric analysis and constant current bulk electrolysis reaction. The exercise lays a practical and theoretical foundation for electrosynthetic reaction and reaction analysis by Nuclear Magnetic Resonance (NMR) spectroscopy for further connection to organic chemistry skills. 3 Khalafi, L.; Cunningham, A. M.; Hoober-Burkhardt, L. E.; Rafiee, M. Why Is Voltammetric Current Scan Rate Dependent? Representation of a Mathematically Dense Concept Using Conceptual Thinking. Chem. Educ. 2021 , 98 , 3957–3961. Goes, S. L.; Mayer, M. N.; Nutting, J. E.; Hoober-Burkhardt, L. E.; Stahl, S. S.; Rafiee, M. Deriving the Turnover Frequency of Aminoxyl-Catalyzed Alcohol Oxidation by Chronoamperometry: An Introduction to Organic Electrocatalysis. Chem. Educ. 2021 , 98 , 600–606. Goes, S. L.; Nutting, J. E.; Hill, N. J.; Stahl, S. S.; Rafiee, Exploring Electrosynthesis: Bulk Electrolysis and Cyclic Voltammetry Analysis of the Shono Oxidation. Chem. Educ. 2022 , 99 , 3242-3248.